Evaluation of Microleakage in Resin Composites Bonded to an Er:YAG Laser and Bur-Prepared Root and Coronal Dentin Using Different Bonding Agents: Microleakage of resin composite to Er:YAG laser and bur-prepared - Shirani, Farzaneh; Birang, Reza; Ahmadpour, Elmira; Heidari, Zeynab; Ostadsharif Memar, Rouzbeh; Zarei, Zahra; Fekrazad, Reza (Journal of Lasers in Medical Sciences, 2021)
Introduction: This study was conducted to assess the microleakage in Er: YAG laser-ablated and burprepared root and coronal dentin cavities using self-etch and total-etch adhesive systems. Methods: Sixty extracted caries-free human third molars were sectioned for dentin exposure. Then, two standard class V cavities were prepared in the root and coronal dentin of each tooth and allocated to one of the following conditioning groups randomly (n=12/Group): G1: Diamond bur for cavity preparation and single bond (BESB) etch-and-rinse adhesive for bonding, G2: Er: YAG laser (160 MJ, 20 Hz, 29.88 J/cm2) and SB (LESB), G3: Er: YAG laser and SB without acid etching (LSB), G4: Diamond bur and Clearfil SE Bond (BCSE) self-etch system, and G5: Er: YAG laser and Clearfil SE Bond (LCSE). The cavities were filled with Z100 composite resin. Dye penetration was assessed after thermocycling. Data analysis was done by Kruskal–Wallis and Mann–Whitney U tests. Statistical significance was set at P<0.05. Results: The results showed there were no statistically significant differences in microleakage between the two preparation methods (bur and laser) or the bonding agents applied (P>0.05). Regardless of the cavity preparation method, dye penetration was significantly higher in coronal dentin than in root dentin (P<0.05). Conclusion: The Er: YAG laser had the same efficacy as the conventional method for cavity preparation, and microleakage did not depend on the bonding agent. Microleakage was significantly higher in coronal restorations than in root restorations. Doi:10.34172/jlms.2021.74.